Georgia Architectural and Historic Properties Survey of Rural [281] Four miles south of Quitman, Valdosta, Ga. December 1980. - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [281] Four miles south of Quitman, Valdosta, Ga. December 1980. Antebellum Greek revival. Two story rectangular plan house. Hipped roof with decorative brackets. Fluted Doric columns - two story monumental portico. Clapboard siding and horizontal siding. Sash windows with 6/6 lights. Interior chimneys. Transom and sidelights underneath decorative alcove. Second story cantilevered balcony. Set on brick piers. Date of Construction: c. 1858-1860. Eudora Plantation is very significant architecturally as a beautiful example of antebellum Greek revival architecture constructed before the civil war. The Plantation is listed on the National Register and has been for about five years. Designed by Mr. Wind for Mr. Jones, a plantation plain floor plan was used. Mr. Jones died before its completion, and his wife's granddaughter, Sarah Jones inherited the house. In 1900, the land was willed to their daughters, Mrs. Ada Paine and Mrs. Elizabeth Smith. In 1883, the Preston Phillips family lived there. No record until 1905 exists. Mr. and Mrs. Jinnin P. Worn (she is a descendant of Francis Jones I) moved into the mansion in order that they might restore it. Restoration began May 28, 1964. At this time it was named Eudora by Mr. Worn after his mother, Emma Eudora Thomas Worn.
Georgia Architectural and Historic Properties Survey of Rural [281] Four miles south of Quitman, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.62 MB (1,702,117 bytes)
Keywords: Valdosta (Ga.); Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.)